Spin coating of capillary tubes. (10th March 2020) - Primkulov, B. K.; Pahlavan, A. A.; Bourouiba, L.; Bush, J. W. M.; Juanes, R.
Abstract : Abstract : We present the results of a combined experimental and theoretical study of the spin coating of the inner surface of capillary tubes with viscous liquids, and the modified Rayleigh–Plateau instability that arises when the spinning stops. We show that during the spin coating, the thinning of the film is governed by the balance of viscous and centrifugal forces, resulting in the film thickness scaling as $h\sim t^{-1/2}$ . We demonstrate that the method enables us to reach uniform micrometre-scale films on the tube walls. Finally, we discuss potential applications with curable polymers that enable precise control of film geometry and wettability.